Tajikistan : Financial Assessment of Barki Tojik - Kochnakyan, Artur; Balabanyan, Ani; Meng, Zhengjia; Verink, Bastiaan (World Bank, Washington, DC, 2014)
This assessment presents the analysis of the financial performance of Barki Tojik (BT), the vertically integrated national power utility of Tajikistan. The assessment is based on the financial model constructed for BT. The assessment relies on projections of BT's financial statements and aims to analyze the financial standing of the company based on its operational performance, solvency and liquidity; forecast the financial performance of the company under various investment scenarios; and assess the cost of domestic power supply. The key findings of the analysis are: 1) the 2012 average weighted billed tariff was significantly lower than the estimated cost of supply; 2) In 2012, the company had a large cash deficit to fully finance the expenses required for domestic supply, the deficit being caused due to high losses, poor collection rates and high general and administrative expenses as well as unclassified costs; 3) timely payments to Independent Power Producers (IPPs) are increasingly becoming an issue; 4) difficulties of BT to service debt will ultimately become a direct burden for the state budget; and 5) significant revenue increase will be required for BT to reach cost-recovery irrespective of long-term investment scenarios pursued.